Impact of rock fracture geometry on geotechnical barrier integrity – A numerical study. (June 2021) - Huber, Florian M.; Leone, Debora; Trumm, Michael; Moreno, Luis R.; Neretnieks, Ivars; Wenka, Achim; Schäfer, Thorsten
Abstract: The effect of fracture geometry on bentonite erosion for a generic repository site in crystalline host rock environment was investigated by means of 2-d numerical simulations. Fracture geometry was varied systematically using random aperture normal distributions with a mean aperture of 1 mm and standard deviations between 0 and 0.7 mm, respectively. Moreover, two aperture correlation lengths (0.2 m and 2 m) were applied. Based on the synthetic fracture aperture fields generated the cubic law in conjunction with the Darcy equation is used to simulate fracture flow fields for mean flow velocities in the fracture between 1 × 10 −5  m/s and 1 × 10 −7  m/s. These flow fields are used in a two-way coupling approach to bentonite erosion simulations. The results of the study clearly show the influence of variable fracture aperture on bentonite erosion behaviour and erosion rates (kg/a). Increasing fracture aperture standard deviation leads to increasing heterogeneous flow velocity distributions governing the erosion behaviour and erosion rates. Calculated steady state erosion rates are in the range of ~0.25 kg/a down to ~0.014 kg/a. The highest erosion rate is calculated for the highest mean flow velocity in conjunction with the highest standard deviation. The effect of aperture heterogeneity diminishes for the lowest flow velocities. In summary, the results show the effect of fracture heterogeneity on bentonite erosion, especially for high to medium mean flow velocities combined with high to medium fracture heterogeneity under the model boundary conditions and model capabilities and limitations considered. An increase of up to ~83% in erosion rate compared to the constant aperture case highlights the need to consider fracture aperture heterogeneity and its effect on the bentonite erosion in the assessment of the safety and evolution of a high-level nuclear waste repository.